Implementation of export potential of national agricultural enterprises - Koval, Bogdan (My University, 2014)
One of the priority directions of the development and presentation of Ukraine in the world is agriculture. Relevance of research due to the fact that in today's global world economy development effective management of the implementation of the export potential of domestic enterprises is one of the key factors for the successful operation of national economy and the development of competitive advantages in foreign markets.
Keywords: agricultural enterprises; agriculture; export potential; сільськогосподарські підприємства; сільське господарство; експортний потенціал; сельскохозяйственные предприятия; сельское хозяйство; экспортный потенциал